Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.3 - Analyzing Graphs of Functions - 2.3 Exercises - Page 197: 99c



Work Step by Step

g(x) = f(x)-2 so, g(-x) = f(-x)-2 = f(x)-2 (as f(x) is even and hence f(x) = f(-x)) Therefore g(x) = g(-x), hence g(x) is even
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.